Hydrothermal Self‐assembly Synthesis of Mn3O4/Reduced Graphene Oxide Hydrogel and Its High Electrochemical Performance for Supercapacitors. Issue 10 (16th September 2013) - Li, Li; Hu, Zhongai; Yang, Yuying; Liang, Pengju; Lu, Ailian; Xu, Huan; Hu, Yingying; Wu, Hongying
Abstract In the present work Mn3O4/reduced graphene oxide hydrogel (Mn3O4‐rGOH) with three dimensional (3D) networks was fabricated by a hydrothermal self‐assembly route. The morphology, composition, and microstructure of the as‐obtained samples were characterized using powder X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), thermogravimetry analysis (TG), atomic absorption spectrometry (AAS), field emission scanning electron microscopy (FESEM) and transmission electron microscope (TEM). Moreover, the electrochemical behaviors were evaluated by cyclic voltammogram (CV), galvanostatic charge‐discharge and electrochemical impedance spectroscopy (EIS). The test results indicated that the hydrogel with 6.9% Mn3O4 achieved specific capacitance of 148 F·g−1 at a specific current of 1 A·g−1, and showed excellent cycling stability with no decay after 1200 cycles. In addition, its specific capacitance could retain 70% even at 20 A·g−1 in comparison with that at 1 A·g−1 and the operating window was up to 1.8 V in a neutral electrolyte.